Idana, Clay County - Regier, Rachel; Beran, Bridget; Golway, Dani (Kansas State University, The Chapman Center for Rural Studies, 2013)
Idana is a small community with a large heart for its church and people. In 1887, the Idana Presbyterian Church began and has remained strong ever since. The church’s centennial in 1987 brought people from Idana back home, traveling from as far as Oregon. Now as they prepare for the 125 anniversary, the people of this town look forward to many festivities with the newly refurbished church building that has been a focal point in this community for over a century.
Rachel Regier, Bridget Beran, Dani Golway, “Idana, Clay County,” Chapman Center Research Collections, accessed October 23, 2020, https://ccrsresearchcollections.omeka.net/items/show/111.
Keywords: Broughton; Clay County; First Presbyterian Church of Idana; Howland; Union Pacific Railroad; Idana